Analisis pengaruh economic value added (EVA), capital structure, total assets turnover dan current ratio terhadap kinerja keuangan pada perusahaan sektor industri dasar dan kimia yang terdaftar di BEI pada Tahun 2017-2019 - Rizky Lombogia Lombogia, Joey; Nelsari Malau, Yois; Rosadi, Faradiva; Grace Monica N, Angel (Jurnal Paradigma Ekonomika, 2021)
This presentation intends to analyze and assess the effect of economic value-added, capital structure, total assets turnover, and current ratio on financial performance. The sample is 39, multiplied by three years, so that the number of observations is 117. The techniques and data used are a purposive sampling of the IDX financial statements from the 2017-2019 period. Partially the economic value-added, capital structure, current ratio are not significant. There is no significant effect while TATO has a substantial impact on financial performance in manufacturing companies in 2017-2019. It can be concluded that EVA and DER CR have no considerable effect while TATO was a significant influence in 2017-2019. Â 